L’entrée sur le marché du travail des finissants du secondaire général: une analyse de leurs besoins d’éducation à la carrière - Dupont, Pierrette; Gingras, Marcelle; Marceau, Denis (Canadian Journal of Counselling and Psychotherapy, 1992)
This article presents the results of a Career Education needs assessment from students finishing their secondary studies who decide to go directly to the world of work compared to those who go on to college education. The answers obtained by Career Education Questionnaire indicates that the two kinds of students express their faith in the importance and the signification of work for themselves and for the Society. On the other hand, the students who go directly to the world of work would have more needs to develop some attitudes of planification and career exploration, and to get more professional information, in order to clarify in a better way their choices or to facilitate their entrance into the active life.